Translation and translating : - Bell, Roger T. (Longman, 1991)
Argues that the subjective evaluation of the product must give way to a descriptive and objective attempt to reveal the workings of the process (ie translating). Without such a shift, translation theory will continue outside the mainstream of intellectual activity in human sciences and fail to take its rightful place as a major field in applied Linguistics